A Comparitive Analysis of Batter Pile Groups under Oblique Loading Conditions - Asha Dominic, Janaki Raman, Samuvel Raj R ,Abishek R R, (International Journal of Advanced Science and Technology, 2020)
Pile foundations are the major part of a high raised structure construction, where the site is comprised of weak soil strata. These types of foundations are mainly subjected to vertical, lateral and combined loading due to the movement of tectonic plates. These lateral loads in addition to vertical loads cause catastrophic structural failure. Batter piles are mostly preferred as an appropriate foundation due to its high load-carrying capacity rather than vertical piles. Many experimental studies have been conducted with oblique loading on batter piles. Experimental studies on batter piles have many drawbacks and don’t provide us with the immediate result for the problem. To rectify the problems in this geotechnical area FEM and FDM software’s are used widely. In this study, a comparative analysis of batter pile groups under oblique and vertical loading using PLAXIS – 3D software is done. The test is conducted with three different batter angles 10˚, 20˚and 30˚ subjected to an uplift load of 60˚ inclination and the load versus settlement curves of different inclinations are compared with the vertical ones. As we see into the results of FEM analysis, the numerical analysis was found to show good agreement to the Experimental study.